2008
DOI: 10.1038/cdd.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine CXCL12 promotes survival of postmitotic neurons by regulating Rb protein

Abstract: Postmitotic neurons need to keep their cell cycle under control to survive and maintain a differentiated state. This study aims to test the hypothesis that the chemokine CXCL12 regulates neuronal survival and differentiation by promoting Rb function, as suggested by previous studies showing that CXCL12 protects neurons from apoptosis induced by Rb loss. To this end, the effect of CXCL12 on Rb expression and transcriptional activity and the role of Rb in CXCL12-induced neuronal survival were studied. CXCL12 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 40 publications
6
87
0
Order By: Relevance
“…Selected experiments were performed using glia-free neuronal cultures as indicated, using previously described protocols (27). Neurons were transfected at the time of plating by Nucleofection (Amaxa), or after 8 days in culture by lipofectamine (Invitrogen), as described previously (4,27). Unless otherwise indicated, all experiments were conducted at 21 DIV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selected experiments were performed using glia-free neuronal cultures as indicated, using previously described protocols (27). Neurons were transfected at the time of plating by Nucleofection (Amaxa), or after 8 days in culture by lipofectamine (Invitrogen), as described previously (4,27). Unless otherwise indicated, all experiments were conducted at 21 DIV.…”
Section: Methodsmentioning
confidence: 99%
“…The chemokine CXCL12 and its cognate receptor CXCR4 perform multiple functions essential for CNS development and function, including guiding migration and differentiation of neuronal precursor cells (1), regulating cell cycle proteins (2)(3)(4), and modulating NMDA receptor signaling (5). These homeostatic functions take on added significance within the context of neuroinflammatory disease, as the CXCL12/CXCR4 signaling axis aids recovery by promoting survival of mature neurons, recruitment of neural and glial progenitor cells (6)(7)(8), and neuronal-glial communication (9).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons were harvested from brain cortices of E17/18 Holtzman rat embryos as previously described (27,29,30). Cells were plated as reported below.…”
Section: Primary Neuronal Culturesmentioning
confidence: 99%
“…Furthermore, data from different groups have shown that SDF-1 and fractalkine are both involved in neuroprotection and regulate excitatory neurotransmission (6,24,25). However, while the neuroprotective effect of fractalkine seems to be related to its ability to counteract microglia-induced neurotoxicity, SDF-1 can directly protect neurons via the activation of its specific receptor CXCR4, which is coupled to major survival pathways, such as the phosphoinositide 3-kinase (PI3K)-Akt pathway (26,27). Interestingly, intracellular pathways stimulated by SDF-1 control transcription factors that up-regulate expression of the fractalkine gene, such as NFB and p53 (28).…”
mentioning
confidence: 99%
“…Neurons can be easily separated from the glial layer at any time during culture and used for different experimental applications ranging from electrophysiology 4 , cellular and molecular biology 5-8 , biochemistry 5 , imaging and microscopy 4,6,7,9,10 . The primary neurons extend axons and dendrites to form functional synapses 11 , a process which is not observed in neuronal cell lines, although some cell lines do extend processes.…”
Section: Introductionmentioning
confidence: 99%